Synthesis of reusable cement materials through photochemical modification of marble powder for composite structures - Ali Zia Noor; Muhammad Atif; Sadia Bibi; Muhammad Burhan Sharif; Amjad Ali (Heliyon)
Sustainability and environmental protection are reshaping industries, including construction, where sustainability plays a crucial role in its influence on global resource consumption and waste management. The current study has developed a reusable cement material by photo-chemical surface modification of marble powder, achieved by reacting glycidyl methacrylate with carbonate functionality. This innovative modified marble powder boosts the reusability of construction materials, unlocking new possibilities for sustainable building practices. By transforming waste into valuable resources, we minimize raw material consumption, foster recycling, and advance circular economy principles in the construction industry. The difference in unmodified (22.9 nm) and modified (23–27 nm) marble powder particle sizes was used to assess the effectiveness of surface modification technique. Compared to non-reusable counterpart (20.34 MPa), the reusability has come at the cost of a decrease in compression stress (11.30 MPa, 10.89 MPa, and 10.57 MPa). Overall, photochemically modified marble powder for its reusability is a groundbreaking approach that offers substantial environmental, economical, and technical advantages, making it an appealing choice for the construction industry.